2023
DOI: 10.1111/jace.19018
|View full text |Cite
|
Sign up to set email alerts
|

Submicron mullite hollow spheres synthesized via UV polymerization of Pickering emulsions

Abstract: We here propose a simple, facile, and effective method to prepare submicron mullite hollow spheres templated from Pickering emulsions. Dual-phase sol consisted of boehmite and silica nanoparticles decorated by pentanoate ion could assemble at water/oil interface irreversibly to form photosensitive Pickering emulsions. The droplets of emulsions could be separated by dilution and formed by photopolymerization to gain hybrid microspheres, which could completely transform to mullite hollow microspheres via binder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…[ 11 ] Kostopoulos et al reported that the tensile strength and failure strain exhibited an abrupt decrease during the early stages of exposure at 1100 °C for 50 h and remained constant thereafter. [ 12 ] In a study by Yang et al, the porosity and compressive strength of an oxide/oxide composite decreased after thermal aging at 1200 °C for 100–500 h. [ 13 ] Long‐term thermally aged oxide/oxide composites have been previously investigated; however, these studies encountered two problems: 1) commercial composites possess two‐dimensional (2D) reinforcements with no fiber in the thickness direction, leading to inadequate delamination resistance under shear loading; [ 14 ] and 2) such studies primarily investigated the relationship between the microstructural evolution and mechanical properties of the composites, and only a few focused on the contribution of the mechanical properties of the constituents to those of the composites after long‐term thermal aging.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Kostopoulos et al reported that the tensile strength and failure strain exhibited an abrupt decrease during the early stages of exposure at 1100 °C for 50 h and remained constant thereafter. [ 12 ] In a study by Yang et al, the porosity and compressive strength of an oxide/oxide composite decreased after thermal aging at 1200 °C for 100–500 h. [ 13 ] Long‐term thermally aged oxide/oxide composites have been previously investigated; however, these studies encountered two problems: 1) commercial composites possess two‐dimensional (2D) reinforcements with no fiber in the thickness direction, leading to inadequate delamination resistance under shear loading; [ 14 ] and 2) such studies primarily investigated the relationship between the microstructural evolution and mechanical properties of the composites, and only a few focused on the contribution of the mechanical properties of the constituents to those of the composites after long‐term thermal aging.…”
Section: Introductionmentioning
confidence: 99%